2004
DOI: 10.1007/s10834-004-5492-y
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Peer Effects in Charitable Giving: The Case of Taiwan

Abstract: The purpose of this study was to utilize the data from the Survey on Family Income and Expenditure in Taiwan to investigate the influence of peer effects on the behavior of charitable giving. Based on the definitions of the reference group in this study, the estimation results suggested that peer effects on households' decisions on both whether to make charitable giving and how much to contribute were quite modest. The study also found that the price elasticity and the income elasticity of charitable giving in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…Brooks (2002) finds no relationship between education and the amount donated to charities in a tobit regression of data from the Consumer Expenditure Survey, controlling for income, wealth, age and welfare income. Wu, Huang and Kao (2004) found no effect of education on the likelihood of giving in Taiwan, though the amount donated was positively related to education. Park and Park (2004) found no relationship between education and donations in Korea.…”
Section: Educationmentioning
confidence: 75%
See 1 more Smart Citation
“…Brooks (2002) finds no relationship between education and the amount donated to charities in a tobit regression of data from the Consumer Expenditure Survey, controlling for income, wealth, age and welfare income. Wu, Huang and Kao (2004) found no effect of education on the likelihood of giving in Taiwan, though the amount donated was positively related to education. Park and Park (2004) found no relationship between education and donations in Korea.…”
Section: Educationmentioning
confidence: 75%
“…Andreoni (2001) and Hodgkinson and Weitzman (1996) find a positive relationship until age 75, after which a decrease is observed. Belfield & Beney (2000), Danesvary and Luksetich (1997), Landry, Lange, Price and Rupp (2006), Midlarsky and Hannah (1989) and Wu, Huang and Kao (2004) find a decrease in giving after the age of 65. In a study with a large proportion of respondents over 65, Schlegelmilch et al (1997a) found a negative relationship of age with the likelihood of giving to charity.…”
Section: Agementioning
confidence: 96%
“…Research has shown that there is a tendency for people in a group to adapt their giving practices to be more similar to those of others in their group [38]. Those participants who are drawn to participate in a charity run event for religious or moral reasons likely already participate in charitable giving at a higher rate than their peers.…”
Section: Increased Entitativitymentioning
confidence: 99%
“…Some data have also suggested that age correlates with other background characteristics, such as income, gender and marital status [98]. While many studies found the existence of a direct relationship between age and giving, some studies reported that the relationship decreased as the donors aged [54,59,96,97]. Therefore, the exact age when giving decreases varies across countries because of the size, age group of the samples, context and giving culture of the society.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Some studies have found a significant relationship between giving and highest degree of education earned [23,103]. However, a study on charitable giving in Taiwan that utilized data from a national survey on family income and expenditures reported that although donations are made for education purposes, education does not relate to giving [96].…”
Section: Level Of Educationmentioning
confidence: 99%